Baseline Chest Computed Tomography as Standard of Care in High-Risk Hematology Patients - Stemler, Jannik; Bruns, Caroline; Mellinghoff, Sibylle C; Alakel, Nael; Akan, Hamdi; Ananda-Rajah, Michelle; Auberger, Jutta; Bojko, Peter; Chandrasekar, Pranatharthi H; Chayakulkeeree, Methee; Cozzi, José A; de Kort, Elizabeth A; et al. (Journal of fungi (Basel, Switzerland), 2020)
Baseline chest computed tomography (BCT) in high-risk hematology patients allows for the early diagnosis of invasive pulmonary aspergillosis (IPA). The distribution of BCT implementation in hematology departments and impact on outcome is unknown. A web-based questionnaire was designed. International scientific bodies were invited. The estimated numbers of annually treated hematology patients, chest imaging timepoints and techniques, IPA rates, and follow-up imaging were assessed. In total, 142 physicians from 43 countries participated. The specialties included infectious diseases (n = 69; 49%), hematology (n = 68; 48%), and others (n = 41; 29%). BCT was performed in 57% (n = 54) of 92 hospitals. Upon the diagnosis of malignancy or admission, 48% and 24% performed BCT, respectively, and X-ray was performed in 48% and 69%, respectively. BCT was more often used in hematopoietic cell transplantation and in relapsed acute leukemia. European centers performed BCT in 59% and non-European centers in 53%. Median estimated IPA rate was 8% and did not differ between BCT (9%; IQR 5-15%) and non-BCT centers (7%; IQR 5-10%) (p = 0.69). Follow-up computed tomography (CT) for IPA was performed in 98% (n = 90) of centers. In high-risk hematology patients, baseline CT is becoming a standard-of-care. Chest X-ray, while inferior, is still widely used. Randomized, controlled trials are needed to investigate the impact of BCT on patient outcome.
Keywords: antifungal prophylaxis; infection in hematology; invasive aspergillosis